SysSU - Um sistema de suporte para computação ubíqua - Lima, Francisco Fabrício de Paula (2011)
The hardware technologies necessary for the realization of Ubiquitous Computing (eg, smartphones, tablets, sensors and smart appliances) have evolved and, today, software components that enable new forms of interaction, able to recognize the face and voice of users, track its location and provide ways to incorporate augmented reality, needed in ubiquitous environments, are being widely developed. In addition, the Software Engineering has evolved to incorporate new development techniques seeking to increase quality and reduce production time of these software artifacts. However, in Ubiquitous Computing difficulties arise in the design of architectures, modeling collaboration among heterogeneous software components, system engineering, and marketing, implementation and validation of the system as a whole. Thus, the development of ubiquitous systems still presents many challenges due to the great diversity and complexity of your requirements. Especially, in ubiquitous environments, where the volatility and heterogeneity of devices, services and applications are common features, and unbound forms of interactions between entities in interoperable distributed software system becomes essential. This volatility and heterogeneity influence the way services are provided in the system, as they are discovered and invoked and how their activities are coordinated to achieve the ultimate goal of the applications. Therefore, this dissertation proposes a new software infrastructure in the form of a support system, called SysSU (System Support for Ubiquity). This support system is shown by a reference architecture and a formal specification. The architecture is based on models Linda and publish / subscribe for the purpose of achieving the desired decoupling. Since the formal specification determines the semantics of the primitives used for the interactions between software components and syntax of the messages exchanged between them in order to standardize implementations. To validate the proposed work, a reference implementation, based on formal specification and architecture, was built. This implementation was used to develop a case study consisting of two separate applications, and UbiPrinter GREat Tour, which exhibit characteristics of volatility and heterogeneity.